Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Café Kenalin Ini Kopi Karawang - Juwita, Ayu; Faddila, Syifa Pramudita (Fakultas Ekonomi Universitas Andalas, 2023)
This study aims to determine: (1) the effect of price on purchasing decisions (2) the effect of product quality on purchasing decisions (3) the effect of price and product quality together on purchasing decisions of Caffe Kenalin, Karawang Coffee. The subjects of this study consisted of 60 customers of Caffe Kenalin's Coffee. Data collection techniques using questionnaires and documentation. Test the validity of the instrument items using Product Moment correlation and reliability testing using Alpha Cronbach. Analysis prerequisite test consists of normality test, linearity test, and multicollinearity test. Data analysis in order to answer research questions consisted of simple regression analysis and multiple regression analysis.